Design of moving message LCD display system (MMDS) via short message service (SMS) entry using rabbit 2000 microcontroller - Badri, Muhamad Atfan (2006)
The aim of this project is to design Moving Message LCD Display System (MMDS) via SMS entry using Rabbit Core Microcontroller 2000 (RCM2000) and integrate it with Global System for Mobile Communication module (GSM). This thesis presents an application of an LCD Display module that can display the message display when the message is sent via mobile phone. The system receives message through Short Message Service (SMS). In order to the send SMS to system, SIM card from Hotlink starter pack had been used. The developed prototype is fully functional and tests have been successful. In conclusion, the MMDS system can replace the conventional entry method using handheld infra red remote console or keyboard. In this thesis, the whole project will be described briefly in each chapter. All results obtained from this study would be beneficial to the MMDS application engineer for future planning and monitoring purposes.